DISTRIBUSI LEMAK ITIK BALI YANG DIBERI JUS DAUN KELOR (MORINGA OLEIFERA) BERPROBIOTIK BAKTERI SELULOLITIK DENGAN LEVEL BERBEDA MELALUI AIR MINUM - Putra A. H.; I. M. Mudita; A. A. P. P. Wibawa (Fakultas Peternakan Universitas Udayana, 2025)
Balinese ducks also have a fairly high calorie content, so it can be said to contain high energy. ducks have a high cholesterol content due to the high special fat contained in duck meat. High and excessive levels of fat and cholesterol can interfere with heart performance and narrowing of blood vessels for people who consume it. Giving feed supplements with probiotics can improve the fat profile and cholesterol levels of duck meat. Providing probiotic feed supplements can improve the quality of nutrient content in the livestock body. For example, Moringa leaves (Moringa oleifera). This study was conducted to determine the effect of the utilization of Moringa leaf juice on the distribution of Balinese duck fat. The design used was a complete randomized design (CRD) consisting of four treatments and four replicates, each replicate consisting of three male Balinese ducks. Treatments consisted of P0 (without provision of probiotic moringa juice), P1 (added 2.5% probiotic moringa juice), P2 (added 5% probiotic moringa juice), P3 (added 7.5% probiotic moringa juice). The observed variables were slaughter weight, bearing fat, mesentery fat, ventriculus fat, and abdominal fat. The results showed that the cutting weight of Balinese ducks in the treatment of 2.5%, 5%, 7.5% had no significant effect compared to P0. The percentage of fat pads, percentage of mesentery fat, percentage of ventricular fat, and percentage of abdominal fat in the P1, P2, and P3 treatments decreased but had no significant effect compared to P0. The results of this study can be concluded that the utilization of 2.5%, 5%, and 7.5% probiotic Moringa leaf juice proved to have no negative effect and did not affect the fat content of the body of Balinese ducks. ABSTRAK Itik bali juga memiliki kandungan kalori yang cukup tinggi,sehingga dapat dikatakan mengandung energi yang tinggi. itik mempunyai kandungan kolestrol tinggi yang disebabkan tingginya lemak khusus yang terkandung pada daging itik. Kadar lemak dan kolestrol yang tinggi dan berlebihan dapat mengganggu kinerja jantung dan penyempitan pembuluh darah bagi orang yang mengkonsumsinya. Pemberian feed suplemen berprobiotik mampu memperbaiki profile lemak dan kadar kolesterol daging itik. Pemberian feed suplement berprobiotik dapat meningkatkan kualitas kandungan nutrien pada tubuh ternak. Contohnya seperti daun kelor (Moringa oleifera). Penelitian ini dilakukan bertujuan untuk mengetahui pengaruh pemanfaatan jus daun kelor berprobiotik terhadap distribusi lemak itik bali. Rancangan yang digunakan adalah rancangan acak lengkap (RAL) yang terdiri dari empat perlakuan dan empat ulangan, setiap ulangan terdiri atas tiga ekor itik bali jantan. Perlakuan terdiri atas P0 (tanpa pemberian jus daun kelor berprobiotik), P1 (ditambahkan 2,5% jus daun kelor berprobiotik), P2 (ditambahkan 5% jus daun kelor berprobiotik), P3 (ditambahkan 7,5% jus daun kelor berprobiotik). Variabel yang diamati adalah berat potong, lemak bantalan, lemak mesenterium, lemak ventrikulus, dan lemak abdomen. Hasil penelitian menunjukan berat potong itik bali pada perlakuan 2,5%, 5%, 7,5% tidak berpengaruh nyata dibanding P0. Persentase lemak bantalan, persentase lemak mesentrium, persentase lemak ventrikulus, dan persentase lemak abdomen pada perlakuan P1, P2, dan P3 terjadi penurunan tetapi tidak berpengaruh nyata dibanding P0. Hasil penelitian ini dapat disimpulkan bahwa pemanfaatan 2,5%, 5%, dan 7,5% jus daun kelor berprobiotik terbukti tidak berefek negatif dan tidak mempengaruhi kandungan lemak pada tubuh itik bali.